Martian Electron Temperatures in the Subsolar Region: MAVEN Observations Compared to a One‐Dimensional Model. Issue 7 (27th July 2018) - Peterson, W. K.; Fowler, C. M.; Andersson, L. A.; Thiemann, E. M. B.; Jain, S. K.; Mayyasi, M.; Esman, T. M.; Yelle, R.; Benna, M.; Espley, J.
Abstract: Prior to the Mars Atmospheric Volatile EvolutioN (MAVEN) mission, altitude profiles of the electron temperature in the Martian thermosphere were measured only twice. Because the rates of several geophysically important processes depend strongly on the electron temperature, models of the Martian thermosphere and atmospheric escape rates have not been well constrained. In this paper, we use densities and temperatures measured by MAVEN instruments and the one‐dimensional model of Matta et al. (2014, https://doi.org/10.1016/j.icarus.2013.09.006 ) to test our understanding of the processes that determine the electron temperature. Our analysis is limited to inbound orbits where the magnetic field is within 30° of horizontal and the satellite is within 30° of the subsolar point at altitudes from 120 to 250 km. We introduce empirically adjusted electron temperatures below 180 km, where the MAVEN electron temperature measurements are known to be biased high. We introduce the concept of a local electron heating efficiency, which we define at a given altitude as the ratio of electron heating from photoionization to the total extreme ultraviolet energy deposited. Our analysis shows that MAVEN observations are consistent with the one‐dimensional model below ~210 km if the electron heating efficiency varies with altitude, and the electron temperature is within the empirical bounds below 180 km we introduced. It indicates that above ~210 km electron heat conduction dominates extreme ultraviolet heating in determining electron temperature. Our analysis also suggests that in the subsolar region electrons and neutrals are in thermal equilibrium below 120 km. Key Points: Densities and temperatures measured by MAVEN are used to evaluate electron heating and cooling terms in a 1‐D energy equation MAVEN observations are consistent with the 1‐D energy equation below ~210 km if the temperature is within the empirical bounds below 180 km The analysis suggests that electrons and neutrals reach thermal equilibrium below 120 km